Literacy: Its Importance and Changes in the Concept and Definition - Ratna Rintaningrum (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Literacy has come to be seen as important aspect in nation development since being functionally literate is fundamental to all forms of both successes in school and in life. In global market, being literate is highly demanded in order that people are able to participate actively in larger society and in International activities such as international conference, research exchange, join research, and business and commerce. Being literate does not only contribute to personal development or personal learning, but being literate also leads to success in school and in life.